PENGARUH SINAR UV TERHADAP pH DAN TOTAL PADATAN TERLARUT NIRA AREN (Arenga pinnata MERR) SELAMA PENYIMPANAN - ANSAR, Ansar Ansar; Sukmawaty, Sukmawaty; Muttalib, Abdul; Wartono, Nopia (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2019)
The purpose of this research was to study the effect of UV light on pH quality and color of palm sap during storage. The materials used in this research was palm sap then this material radiation by the light of UV in the coolbox. The radiation given for two sample, first sample for palm sap morning tapping and the second is palm sap afternoon tapping with the variation of the uv light is 3, 6, and 9 watt and the time for radiation is 30, 60, and 90 minute. The parameters observed by this reaseach are pH, brix, and color. pH value counted by pH metter, refractometer for brix’s value, and hunter Lab for the color of palm sap. The result showed that, palm sap unradiation having decrease a lot from palm sap with radiation. Along with a decrease in the quality of pH, brix levels in each sample palm sap weren’t having significantly changed but showed the fluktuaktif value. Color of palm sap, L* (lightness) value having increase and a* (redness) with b* (yellowness) having decrease all of them. The decrease in pH quality of 0.38 was smaller than that of the palm sugar sap without irradiated at 0.53.